Mandibular aspergilloz: Nadir bir osteomyelit olgusu - (:unkn) unknown (My University, 2007)
Aspergillus türü saprofit mantarlardan olup, özellikle bağışıklık sistemi baskılanmış hastalarda enfeksiyon kaynağı olarak bilinmektedir. Aspergillus genellikle solunum sistemini tutmakta ve kemik invazyonu nadir olarak gözlenmektedir. Literatürde mandibulanın aspergillus türü ile osteomyeliti yalnız iki vakada bildirilmiştir. Tedavi seçenekleri arasında en yaygın kullanılanı antimikrobiyal tedavinin cerrahi ile kombinasyonudur. Burada, multipl myelom tedavisi için immünsüpresif terapi altında olan ve mandibulasında aspergilloz gelişen bir hasta bildirilmektedir.

Aspergillus species are saprophyticus fungi which may be the cause of infection predominantly in immunocompromised hosts. Aspergillosis is usually manifested in the respiratory system and bone involvement is rarely encountered. Osteomyelitis of the mandible with aspergillus species has been reported in only two cases in the literature. Treatment mainly consists of antimicrobial therapy in combination with surgery. We report a case of aspergillosis of the mandible in a patient who was under immunosuppresive treatment for multiple myeloma at the time of diagnosis.
Aspergillosis of mandible: A rare case of osteomyelitıis